2
$\begingroup$

Let $z,w \in \Bbb C$.

Prove $|z+iw|^2 + |w+iz|^2 = 2 (|z|^2 + |w|^2)$

When i solve the left side of the above equation i get stuck with $2i(z\bar w + z\bar w)$.

if you could please help me with this. Thanks in advance.

V.

$\endgroup$
  • $\begingroup$ How are you solving the left side of the equation? Are you using $\vert z+iw\vert^2=\overline{(z+iw)}(z+iw)=(\overline{z}-i\overline{w})(z+iw)$? $\endgroup$ – Sam Jaques Jan 31 '17 at 20:44
  • $\begingroup$ i am doing $|z+iw|^2 = (z+iw)(\bar z + i\bar w)$ $\endgroup$ – ISuckAtMathPleaseHELPME Jan 31 '17 at 20:46
  • $\begingroup$ You need to conjugate every term, which includes $i$. The conjugate of $i$ is $-i$; hopefully that will cancel everything out. $\endgroup$ – Sam Jaques Jan 31 '17 at 20:49
  • $\begingroup$ it worked! thank you.I was unaware of the conjugate of i = -i $\endgroup$ – ISuckAtMathPleaseHELPME Jan 31 '17 at 20:53
2
$\begingroup$

Hint

$$|z+iw|^2=(z+iw)(\overline{z}-i\overline{w})=z \overline{z}+iw\overline{z}-iz\overline{w}+w\overline{w}=|z|^2+|w|^2+i(w\overline{z}-z\overline{w})$$

Do the same for

$$|w+iz|^2=(w+iz)(\overline{w}-i\overline{z})$$

And get what you want.

Ps.: I'm using that $|k|^2=k\cdot \overline{k}$

$\endgroup$
3
$\begingroup$

Use $|a+b| = |a|^2 + \bar a b + a \bar b + |b|^2$. Then $$|z + iw|^2 = |z|^2 + \bar z (iw) + z(\overline{iw}) + |iw|^2 = |z|^2 + i \bar z w - i z\bar w + |w|^2$$ and $$|w + iz |^2 = |w|^2 + \bar w (iz) + w(\overline{iz}) + |iz|^2 = |w|^2 + i \bar w z - i w\bar z + |z|^2.$$ Now add.

$\endgroup$
2
$\begingroup$

Just calculate straight forward

$|z+iw|^2 + |w+iz|^2=(z+iw)(\overline{z} - i\overline{w})+(w+iz)(\overline{w}-i\overline{z})= |z|^2 -i\overline{w}z+iw\overline{z}+ |w|^2 +|w|^2 -i\overline{z}w +i\overline{w}z + |z|^2 = 2 (|w|^2 + |z|^2) $

$\endgroup$
0
$\begingroup$

For a geometric interpretation of the formula, note that the equality is homogeneous in $z,w$ so it can be assumed WLOG that $w=1$. Also, $|1+iz|=|i||z-i|=|z-i|$ so the equality becomes:

$$|z+i|^2 + |z-i|^2 = 2 |z|^2 + 2 \quad \iff \quad |z|^2 = \cfrac{|z+i|^2+|z-i|^2}{2} - \cfrac{2^2}{4}$$

But the latter is simply the median length formula in the triangle defined by $z,i,-i$ with side lengths $|z-i|,|z+i|,2$ and median length $|z|\,$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.